System-level modelling and design space exploration for multiprocessor embedded system-on-chip architectures - Erbaş, Çağkan (ASCI dissertation series, 2006)
Modern embedded systems come with contradictory design constraints. On one hand, these systems often target mass production and battery-based devices, and therefore should be cheap and power efficient. On the other hand, they still need to show high (some.